2005
DOI: 10.1249/01.mss.0000175857.84936.1a
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Lymphocyte Activation following Chemotherapy for Breast Cancer

Abstract: Exercise may improve immune function by increasing lymphocyte activation in patients with breast cancer following treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(139 citation statements)
references
References 24 publications
(24 reference statements)
3
126
0
6
Order By: Relevance
“…These findings are clinically significant as patients post chemotherapy and radiotherapy often gets secondary infections. So a moderate level of exercise regime can be effective in boosting immunity [40]. Similar results were observed by Waart et al, were they utilised exercises to minimise the decline in cardiorespiratory fitness, muscle strength and fatigue while undergoing chemotherapy.…”
Section: Physiotherapysupporting
confidence: 65%
See 1 more Smart Citation
“…These findings are clinically significant as patients post chemotherapy and radiotherapy often gets secondary infections. So a moderate level of exercise regime can be effective in boosting immunity [40]. Similar results were observed by Waart et al, were they utilised exercises to minimise the decline in cardiorespiratory fitness, muscle strength and fatigue while undergoing chemotherapy.…”
Section: Physiotherapysupporting
confidence: 65%
“…Cancer patients (40) and nonc a n c e r patients (33) Scrambler therapy was given daily for 30 min for 5 days in a week for 2 weeks. A 2 weeks follow up was done at the end of treatment.…”
Section: N=73mentioning
confidence: 99%
“…Despite its growth, the authors did not find statistically significant differences between trained and untrained groups (13). Hutnick et al, Demarzo et al, as well Mathur and Pedersen showed an increase in lymphocytes count and their activity in the peripheral blood together with increased physical activity (12,15,38). Lima et al compared the tumor mass and cell proliferation in trained and untrained rats.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that in animals physically active at puberty (rodent treadmill, tunnels and ladders), the risk of developing the disease is decreased, the possible tumor development is delayed and smaller-sized tumors are observed (5)(6)(7)(8)(9)(10)(11). Currently, a longer survival time is observed in individuals after cancer treatment who regularly exercise (12)(13)(14)(15)(16)(17) (23,24). Fairey et al found an increase in the number of NK cells in the blood of women who trained and had previously undergone breast cancer treatment (13).…”
mentioning
confidence: 99%
“…Evidence includes a substantial number of peer-reviewed articles on the benefits of exercise alone and greatly supports the use of rehabilitation interventions in various cancer populations 12 . Systematic analysis of that research shows a positive effect at all stages of disease for reducing fatigue [13][14][15] ; improving tolerance to treatment [16][17][18] ; significantly improving time to recovery 19 and sleep 20 ; and enhancing immune function 21 , cardiovascular function 15 and health-related quality of life 18,22 . Reports of positive outcomes are mounting 23 , and it has become imperative to develop models of care that systematically include rehabilitation and exercise prescription.…”
Section: Introductionmentioning
confidence: 99%